A simple and general approach for in situ synthesis of sulfur–porous carbon composites for lithium–sulfur batteries. Issue 12 (14th October 2019) - Díez, Noel; Ferrero, Guillermo A.; Sevilla, Marta; Fuertes, Antonio B.
Abstract : Biomass-derived carbon/sulfur composites are synthesized by a simple approach using sodium thiosulfate as both the activating agent and sulfur source. Abstract : Porous carbon materials constitute an excellent conductive matrix for the immobilization of sulfur in the cathode of lithium–sulfur batteries. Herein, we provide a novel, easy, sustainable, general and scalable procedure for the preparation of such cathodes, which combines in the same process both the generation of a S-doped porous carbon and the incorporation of elemental sulfur within the pores. To achieve this, a biomass-based substance ( i.e., tannic acid) is activated with sodium thiosulfate, yielding a carbonized solid that includes a high-surface area carbon (up to 2550 m 2 g −1 ) and sodium polysulfides. Once this solid is immersed in an acid medium, the polysulfides generated as activation by-products are oxidized in situ to elemental sulfur that spontaneously diffuses into the pores of the carbon, which gives rise to the hybrid sulfur–carbon composite. When tested as cathodes in lithium–sulfur batteries, these hybrid materials exhibit high sulfur utilization (∼80%) even for the composites with a sulfur content as high as 82%, as well as an excellent rate performance (590 mA h g −1 S at 5C). The cycling stability of the batteries was confirmed by their low capacity fading (0.049% of capacity decay per cycle), maintaining 85% of their initial capacity after 300 charge–discharge cycles at 1C. Cathodes with a high sulfur loading (7.1 mg S per cm 2 ) were steady cycled providing reversible areal capacities of 4.4 mA h cm −2 at 0.2C after 100 charge–discharge cycles.